Concrete solar collectors for façade integration: An experimental and numerical investigation. (15th November 2017) - O'Hegarty, Richard; Kinnane, Oliver; McCormack, Sarah J.
Highlights: Precast concrete cladding systems can be converted into concrete solar collectors by embedding pipes in the concrete. A real time experimental set-up of a concrete solar collector is presented for Dublin. Concrete solar collectors can provide significant energy for preheating applications. A 3D numerical model is successfully validated against experimental results. The numerical model highlights solar absorptance and collector area as key performance parameters. Abstract: Precast concrete cladding systems can be converted into concrete solar collectors by embedding pipes within the exposed concrete, providing a unique building integrated solar thermal solution. Past research of non-integrated, roof-attached concrete solar collectors have largely focused on experimental studies in high temperature climates and/or simulation studies using simplified 1D and 2D models. This study (1) Experimentally investigates the performance of a façade integrated concrete solar collector in a mid-latitude European climate (Dublin) and (2) Develops and validates a 3D numerical model which is then used to predict the performance of other façade integrated concrete solar collectors in other European climates. The study primarily quantifies the performance in relation to the energy output and the solar fraction. The experimental set-up of the concrete solar collector is designed to represent a south facing façade installation. The experimental results showed that one quarter of the annual hot water demand of a single occupant dwelling could be provided using 1 m 2 of concrete solar collectors with spring and autumn months producing the highest daily energy outputs; attributed to the vertical orientation of the concrete solar collectors. A 3D numerical model of the vertically installed concrete solar collector is developed in COMSOL Multiphysics and validated against the experimentally measured results. The validated model is used to expand the study to different collectors and systems, as well as two additional contrasting Northern and Southern European climates where precast concrete is a popular cladding material, namely Helsinki and Sofia. The simulation results showed that the solar absorptance, flow rate, collector area and pipe length have a significant influence on the performance of the concrete solar collector system. Annual solar fractions of 20% (Helsinki), 24% (Dublin) and 30% (Sofia) are predicted for a small apartment building using a façade integrated concrete solar collector. The concrete solar collectors presented a negligible influence on the interior environment provided sufficient insulation is located at the back of the concrete absorber, as would be typical of a precast concrete sandwich panel construction.